The value derived from a practice: An application to the case of energy savings. (June 2020) - Innocent, Morgane; François-Lecompte, Agnès
This research proposes a framework for value analysis derived from a practice. We link this concept with the consumer value in marketing. The approach adopted for the value derived from a practice is bivalent, including the various reasons for valuing and devaluing the activity. We then propose a model based on the assumption that the value derived from a practice changes with the intensity of the practice. The empirical study focuses on the practice of eco-friendly gestures that aim to save electricity. The results show that the more intensified the practice, the stronger the value creation while the loss of value is reduced. In addition, a multi-group analysis allows the diversification of the value to be observed when the intensity of the practice increases. The results reveal the importance of eudemonic value, which offers a new avenue for understanding the mechanisms of appropriation of practices with societal stakes.